2016
DOI: 10.2139/ssrn.2932341
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Energy, Bioenergy, and Agricultural Commodity Prices: Re-Considering Structural Changes

Abstract: This study investigates the relationships among the prices of gasoline, ethanol, and agricultural products that includes soybeans and corn. By increasing production of ethanol using corn, concerns about emerging new relationship between agricultural products price and energy price increased. The result indicates that, without considering structural breaks, there is no long-run relationship between energy and agricultural products prices. However, after consideration of structural breaks not only, long-run rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Myers et al (2014)studied the comovements between feedstock and energy prices and found no comovements between these prices in the long run. Nemati (2016) investigated the relationships among the prices of gasoline, ethanol, and agricultural products that included soybeans and corn, using monthly data from January 1986 to November 2014. The result indicated that there was a relationship between energy and agricultural product prices and this relationship intensified during the last decade.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Myers et al (2014)studied the comovements between feedstock and energy prices and found no comovements between these prices in the long run. Nemati (2016) investigated the relationships among the prices of gasoline, ethanol, and agricultural products that included soybeans and corn, using monthly data from January 1986 to November 2014. The result indicated that there was a relationship between energy and agricultural product prices and this relationship intensified during the last decade.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Adaptation to the demand-driven mechanism caused by speculative price manipulation, including input, is severely affected by the limitation of the level of flexibility often incompatible with the characteristics and potential of agricultural production and the degree of effective absorption in the market. Analysing the relationship between energy prices and agricultural products by applying the self-regressive vector model (VECM), Nemati (2017) clearly demonstrates the existence of a long-term decisive relationship between these price categories, especially an intensification for the period 2007-2014.…”
Section: Introductionmentioning
confidence: 99%
“…This has profound practical significance and important value for promoting the iterative innovation of the corn industry and the increase of corn production income. At present, after summarizing the problems and lessons in the past, the corn futures market in our country continues to increase in scale and the market operation is becoming more stable [11].…”
Section: Introduction To Corn Futures and Corn Futures Marketmentioning
confidence: 99%